Biallelic mutations in DYNC2LI1 are a rare cause of Ellis‐van Creveld syndrome. Issue 3 (24th January 2018) - Niceta, M.; Margiotti, K.; Digilio, M.C.; Guida, V.; Bruselles, A.; Pizzi, S.; Ferraris, A.; Memo, L.; Laforgia, N.; Dentici, M.L.; Consoli, F.; Torrente, I.; et al.
Abstract : Ellis‐van Creveld syndrome (EvC) is a chondral and ectodermal dysplasia caused by biallelic mutations in the EVC, EVC2 and WDR35 genes. A proportion of cases with clinical diagnosis of EvC, however, do not carry mutations in these genes. To identify the genetic cause of EvC in a cohort of mutation‐negative patients, exome sequencing was undertaken in a family with 3 affected members, and mutation scanning of a panel of clinically and functionally relevant genes was performed in 24 additional subjects with features fitting/overlapping EvC. Compound heterozygosity for the c.2T>C (p.Met1?) and c.662C>T (p.Thr221Ile) variants in DYNC2LI1, which encodes a component of the intraflagellar transport‐related dynein‐2 complex previously found mutated in other short‐rib thoracic dysplasias, was identified in the 3 affected members of the first family. Targeted resequencing detected compound heterozygosity for the same missense variant and a truncating change (p.Val141*) in 2 siblings with EvC from a second family, while a newborn with a more severe phenotype carried 2 DYNC2LI1 truncating variants. Our findings indicate that DYNC2LI1 mutations are associated with a wider clinical spectrum than previously appreciated, including EvC, with the severity of the phenotype likely depending on the extent of defective DYNC2LI1 function. Abstract :